Energy-Efficient Computing and Networking First International Conference, E-Energy 2010, First International ICST Conference, E-Energy 2010 Athens, Greece, October 14-15, 2010 Revised Selected Papers - Hatziargyriou, Nikos; Dimeas, Aris; Tomtsi, Thomai; Weidlich, Anke (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2011)
This book constitutes the postproceedings of the First International Conference on Energy-Efficient Computing and Networking, E-Energy, held in Passau, Germany in April 2010. The 23 revised papers presented were carefully reviewed and selected for inclusion in the post-proceedings. The papers are organized in topical sections on energy market and algorithms, ICT technology for the energy market, implementation of smart grid and smart home technology, microgrids and energy management, and energy efficiency through distributed energy management and buildings.